Improved effective dynamics of loop-quantum-gravity black hole and Nariai limit. (17th January 2022) - Han, Muxin; Liu, Hongguang
Abstract: We propose a new model of the spherical symmetric quantum black hole in the reduced phase space formulation. We deparametrize gravity by coupling to the Gaussian dust which provides the material coordinates. The foliation by dust coordinates covers both the interior and exterior of the black hole. After the spherical symmetry reduction, our model is a 1 + 1 dimensional field theory containing infinitely many degrees of freedom. The effective dynamics of the quantum black hole is generated by an improved physical Hamiltonian H Δ . The holonomy correction in H Δ is implemented by the μ ¯ -scheme regularization with a Planckian area scale Δ (which often chosen as the minimal area gap in loop quantum gravity). The effective dynamics recovers the semiclassical Schwarzschild geometry at low curvature regime and resolves the black hole singularity with Planckian curvature, e.g. R μνρσ R μνρσ ∼ 1/Δ 2 . Our model predicts that the evolution of the black hole at late time reaches the charged Nariai geometry dS2 × S 2 with Planckian radii ∼ Δ . The Nariai geometry is stable under linear perturbations but may be unstable by nonperturbative quantum effects. Our model suggests the existence of quantum tunneling of the Nariai geometry and a scenario of black-hole-to-white-hole transition.